Food Neophobia and Consumer Choices within Vietnamese Menu in a Polish Cohort Study - Guzek, Dominika (Int J Environ Res Public Health, 2021)
One of the factors influencing consumer food choices is food neophobia (FN), described as a reluctance to try novel or unknown food products. The aim of the study was to determine the influence of FN on food choices in young Polish respondents through a web-based choice experiment with Vietnamese restaurant menu. The choice experiment was conducted using a Computer-Assisted Web Interview (CAWI) method in a sample of 601 young adults, while using a developed Vietnamese restaurant menu. For the dishes, neophobic potential for a Polish population was defined, based on content of ingredients not typical for Polish diet. The FN was assessed using the Food Neophobia Scale (FNS) by Pliner and Hobden. The neophobic potential was the determinant of choice of dishes (p < 0.05). The participants characterized by a high FN level less commonly than others chosen dishes characterized by neophobic potential as: starter (Nem quõn—non-fried spring rolls with shrimps) (p = 0.0003), soup (Mién gà—soup with cellophane noodles and nam huong mushrooms) (p < 0.0001), main course (Phở xào bò—rice noodles with soy sauce and fish sauce) (p < 0.0001) and dessert (Chè thập cãm—dessert of golden gram, black eye beans, Azuki beans and tapioca) than other options (p = 0.0007). It was stated that FN in young respondents may reduce the frequency of choosing dishes containing unfamiliar ingredients and, as a result, it may cause lower diversity of consumed dishes. Taking into account that not properly balanced diets resulting from rejecting some types of products are becoming a growing problem, the FN should be taken into account in the general public health policy.